Perfil de funcionalidade e incapacidade de crianças brasileiras com risco e provável transtorno do desenvolvimento da coordenação (TDC) - Beliche, Thiago Weyk de Oliveira (Universidade Federal de São Carlos, 2025)
Developmental Coordination Disorder (DCD) is a neurodevelopmental disorder characterized by motor performance below expectations, affecting approximately 5% to 8% of school-age children. The International Classification of Functioning, Disability and Health (ICF), as well as current care guidelines for DCD, propose a comprehensive description of the functional profile of individuals. This thesis was developed considering gaps in the understanding of biopsychosocial components relevant to the health of children with this condition and comprises three scientific studies, as described below. Study 1 – Objective: To conduct a scoping review of the literature exploring the main characteristics and determinants of participation in children with DCD. Methods: The MEDLINE/PubMed, Scopus, CINAHL, and Web of Science databases were searched for studies published between 2001 and 2021 that evaluated participation and/or related constructs in children with DCD aged 5 to 17 years. Studies were selected by two independent researchers. Data were extracted using standardized forms and synthesized by consensus. Study quality was assessed using the Mixed Methods Appraisal Tool (MMAT). Results: A total of 2,444 studies were identified, and 14 met the inclusion criteria—all from high-income countries. The studies involved children with a mean age of 9.7 years and used appropriate diagnostic criteria and validated instruments to assess participation. Children with DCD demonstrated reduced participation levels compared to typically developing peers, especially in physical and social activities, with lower involvement in sports teams, leisure activities, and reduced parental satisfaction. Conclusion: While there is consistent evidence of reduced participation in children with DCD, knowledge gaps remain regarding participation within family and school environments. Research is needed to identify contextual determinants of participation to guide effective interventions. Study 2 – Objective: To compare the functional profile of children at risk of (r-DCD) or with probable DCD (p-DCD) and those with typical neurodevelopment (TND), based on the biopsychosocial model. Methods: This analytical cross-sectional study was conducted in a municipality in southern Brazil, following STROBE recommendations. Children were classified into TND, r-DCD, and p-DCD groups based on MABC-2 results. Assessment tools covered the four ICF domains: body functions (MABC-2, 6-Minute Walk Test), activities (DCDQ-Brazil, IPAQ-SF), participation (PEM-CY), and contextual factors (SDQ-Portuguese; PEM-CY environmental scales). Statistical analysis included the Kruskal–Wallis test and Dunn’s post-hoc test (α=0.05). Results: The sample included 208 children (mean age 8.25 ± 1.28 years; 94 girls), with TND (n=158), r-DCD (n=25), and p-DCD (n=25). As expected, the p-DCD group had significantly lower motor scores. In the participation domain, p-DCD children reported lower community involvement than r-DCD children (p=0.016). No significant differences were observed in other ICF components. Conclusion: The main impact of DCD was identified in the ICF participation domain. This study broadens understanding of the functioning of children with DCD and emphasizes the need for future research on determinants of functioning in this population. Study 3 – Primary Objective: To compare the motor performance of children from the five Brazilian regions. Secondary Objective: To explore associations between sociodemographic variables and motor performance. Methods: This multicenter cross-sectional study included 967 children (6–10 years old) from public schools in five Brazilian regions: South (n=208), Northeast (n=92), Southeast (n=232), Midwest (n=243), and North (n=192). Motor performance was assessed using MABC-2. Sociodemographic data were collected via caregiver questionnaire. Regional comparisons were made using the Kruskal Wallis test. Correlations between MABC-2 scores and family income, maternal and paternal education were analyzed using Spearman’s ρ (α=0.05). Results: Regional differences in motor performance were observed. Children from the Northeast and Midwest had lower scores in manual dexterity. The North region showed higher aiming and catching scores, while the Northeast had the lowest. In the balance domain, children from the Northeast outperformed others. No significant correlations were found between MABC-2 scores and family income or parental education. Conclusion: The significant variations in motor performance of children from different regions of Brazil suggest a possible effect of environmental variables. However, sociodemographic factors were not significant for performance. It is speculated that they possibly influence other determinants of this performance in a complex way. Thus, it is recommended that future research investigate other environmental factors that may have an impact on motor performance. Taken together, the results of this thesis provide information on little- discussed components of the functioning of children with DCD, highlighting the need to monitor involvement in relevant community activities. Furthermore, paths are pointed out for future studies to identify contextual targets to be considered when evaluating and proposing interventions aimed at children with this condition.
Functionality and disability profile of Brazilian children at risk of or with probable developmental coordination disorder (DCD)
Keywords: Classificação Internacional de Funcionalidade, Incapacidade e Saúde; Crianças; Participação; Transtorno do desenvolvimento da coordenação; Habilidades motoras; International Classification of Functioning, Disability and Health; Children; Participation; Developmental coordination disorder; Motor Skills; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL